Pemberdayaan Masyarakat melalui Pelatihan Pemasaran Produk Udang Kasia untuk Meningkatkan Perekonomian di Kampung Arar, Kabupaten Sorong - Sulfiana; Ibal, La; Abu, Nur; Rahayu, Andi; Rahmi; Murni; Kayatun, Siti Nur; Saleh, Muhammad; Masniar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The marketing training for cassia shrimp products held in Arar Village, Sorong Regency, Southwest Papua aims to improve community skills in overcoming obstacles to marketing local products. This activity is carried out through three stages: preparation, implementation, and evaluation. In the initial stage, the team coordinated with village officials to understand local conditions and the economic potential of the community. The implementation stage focused on digital marketing training and product packaging techniques, followed by pretests and posttests to measure skill improvements. The results of the training showed a significant increase in participants' understanding of online marketing strategies, the importance of information on packaging, and factors that can attract consumer interest and loyalty, such as attractive packaging design and product taste quality. Before the training, the majority of participants still used traditional marketing methods, but after the training, 89.47% of participants switched to digital marketing. This training succeeded in providing an understanding of broader and more modern marketing strategies, so that the community is better prepared to compete in a larger market. The impact is seen in the increase in sales, income, and sustainable economic potential in Arar Village